Elovl5 is required for proper action potential conduction along peripheral myelinated fibers. Issue 10 (17th June 2021) - Hoxha, Eriola; Balbo, Ilaria; Parolisi, Roberta; Audano, Matteo; Montarolo, Francesca; Ravera, Francesco; Guglielmotto, Michela; Muratori, Luisa; Raimondo, Stefania; DiGregorio, Eleonora; Buffo, Annalisa; Brusco, Alfredo; et al.
Abstract: Elovl5 elongates fatty acids with 18 carbon atoms and in cooperation with other enzymes guarantees the normal levels of very long‐chain fatty acids, which are necessary for a proper membrane structure. Action potential conduction along myelinated axons depends on structural integrity of myelin, which is maintained by a correct amount of fatty acids and a proper interaction between fatty acids and myelin proteins. We hypothesized that in Elovl5 −/− mice, the lack of elongation of Elovl5 substrates might cause alterations of myelin structure. The analysis of myelin ultrastructure showed an enlarged periodicity with reduced G‐ratio across all axonal diameters. We hypothesized that the structural alteration of myelin might affect the conduction of action potentials. The sciatic nerve conduction velocity was significantly reduced without change in the amplitude of the nerve compound potential, suggesting a myelin defect without a concomitant axonal degeneration. Since Elovl5 is important in attaining normal amounts of polyunsaturated fatty acids, which are the principal component of myelin, we performed a lipidomic analysis of peripheral nerves of Elovl5‐deficient mice. The results revealed an unbalance, with reduction of fatty acids longer than 18 carbon atoms relative to shorter ones. In addition, the ratio of saturated to unsaturated fatty acids was strongly increased. These findings point out the essential role of Elovl5 in the peripheral nervous system in supporting the normal structure of myelin, which is the key element for a proper conduction of electrical signals along myelinated nerves. MAIN POINTS: Consequences on peripheral nerves of Elovl5 deletion: Unbalance between saturated versus unsaturated fatty acids in membrane phospholipids. Loss of myelin compactness Slower action potential conduction